Food purchase patterns, food policy recognition, and food environment satisfaction among adults in Jeju, Korea, according to food security: a cross-sectional study - Sumin Kim; Youjeong Jang; Hyunji Ham; Hanbin Ko; Insuk Chai; Kyungho Ha (Korean Journal of Community Nutrition)
Objectives Recently, food insecurity has been a major public health issue along with the food crisis caused by COVID-19, climate change, and the polarization of food supply due to socioeconomic disparities. Food insecurity is known to be related to the food choices and environment of the consumer. Therefore, this study aimed to evaluate the food security statuses of adults in Jeju and investigate their food purchase patterns, food policy recognition, and food environment satisfaction. Methods Based on data from the 2022 Jeju Food Survey, 346 adults aged ≥ 19 years in Jeju were classified into food security and insecurity groups (quantitatively and qualitatively) using the questionnaire. Food purchase patterns, including purchasing frequency, items, and reasons, were surveyed for local and eco-friendly foods. The recognition and necessity of several food policies and satisfaction with diet and food environment (availability, accessibility, affordability, accommodation, and acceptability) were measured using the Likert scale. Results Among the total participants, 47.4% were in the food insecurity group. The frequency of purchasing local and eco-friendly foods did not significantly differ by food security status. The insecurity group exhibited a higher recognition rate of basic rights to food (36.0%) than the security group (24.7%, P = 0.023). The recognition and necessity of specific food policies did not significantly differ by food security status, except for the policy of promoting food communities, for which the food security group exhibited higher recognition than the food insecurity group did (P = 0.004). The food insecurity group exhibited significantly lower scores regarding satisfaction toward diet and food environment factors (P < 0.05 for all). Conclusion Overall, the food security group reported higher satisfaction with their diet and food environment than the food insecurity group. Further in-depth studies to investigate the determinants of food insecurity and effective promotional strategies for food policies are needed.